VIOLÊNCIA DENUNCIADA CONTRA CRIANÇAS E ADOLESCENTES, NOS CONSELHOS TUTELARES DE FEIRA DE SANTANA - BA, 2003-2004. - Barbara, Josele de Farias Rodrigues Santa (2006)
The violence against children and adolescents has been considered an important question of public health, in the different countries and socio-cultural contexts, occupying place of prominence in the directed international politics to the Human Rights. Objective: to characterize the violence against children and adolescents, how much to the aspects related to the victims and aggressors. Materials and Method: One is about a transversal study, with secondary data of the registers of the denunciations of violence against children and adolescents, in the Advice To tutor I and II of the city of Fair of Santana, in the period of 2003 and 2004. The data had been collected through a form, consisting changeable partnerdemographic related the child and vitimizados adolescents, to familiar and the aggressive ones; characterization of the violence forms; e encaminhamentos in the Net of Attendance. Analyses had been carried through descriptive, through the calculation of the absolute and simple frequencies, as well as bivaried analysis, through the association between etária band ((1 year; 2-5 years; 6-9 years; 10-13 years; 14-16 years; e 17-19 years complete) and sex of the adolescent child, with other 0 variable related to the forms of violence and characterization of the aggressors. Results: They had totalized 1293 registers of denunciations of violence against children and adolescents, in the Advice To tutor I and II. The place of bigger occurrence of these 27 registers was the domicile with 1011 (78.1%) of the registers. The types of more frequent violências had been the recklessness, the physical violence and the psychological violence; more frequently in the 2-5 bands years, 6-9 years and 10-13 years, and important ratios in minors of 1 year. The sexual violence presented greater prevalence between adolescents, much even so with registers in all the other bands of age. The different forms of violence had been equivalents between the sexos. The data of etnia and escolaridade of the victims had presented decreases ratio and registers, compromising the analysis. The main source of denunciation was anonymous 398 (30.8%). The mother was the main aggressor, with 646 (47.7%) of the registers of physical, psychological violence and familiar recklessness. The data related to the age and state of conscience of the aggressor did not meet in the registers. Final Considerations: The results of this research had pointed with respect to the necessity of sensitization and formation of the professionals of the Net how much to the register of important 0 variable, on to the ethnic aspects, among others, searching the improvement in the quality of the registers in the Advice To tutor; as well as the necessity of complementary research, with primary data and minute analyses, in view of contributing with the actions of confrontation and spreading of it It dials Denunciation ; important subsidy it to be able public and local institutions, in the elaboration of politics directed to the social development, protection and prevention of the violence, as well as in the qualification of the attendance of the cases for the Net.